Крик волка: роман / А. М. Дышев ; худож. Г. И. Сауков - Дышев Андрей Михайлович (Черная кошка, 1995)
Экземпляры: аб. ЦБ (20200917) / Инвентарный номер: 9806 / Цена: / Сис.шифр: 84(2)6 / Авт.знак: Д 91 / ББК: 84(2)6